Analisis Tindak Tutur Lokusi pada Daftar Putar “Kisah Tokoh Inspiratif” dalam Kanal Youtube Zenius - Fina Fadhilatul Amalia; Gisella Orlanova Ramadhanti; Aulia Rahayu; Muhamad Taufiq Hamdani; Iyas Rahmawati; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Living humans cannot be separated from language to communicate. Communication is carried out by expressing what the speaker will convey to his speech partner through speech acts. Speech acts themselves have various types, starting from locutionary, illocutionary, and perlocutionary. The main focus of this research is the use of locutionary speech acts in the "Stories of Inspirational Figures" playlist on the Zenius YouTube channel, which is one of the currently popular educational channels. The main aim of this research is to explain the form of locutionary speech acts contained in the playlist "Zenius: Kisah Tokoh Inspiratif". This research uses a qualitative descriptive research method, with a pragmatic theoretical approach. The data collection technique uses listening and note-taking techniques, the data analysis technique uses the collection method, and the data presentation technique is informal, namely using ordinary words. The results obtained from the analysis of a collection of videos in the "Stories of Inspirational Figures" playlist on the Zenius YouTube channel are 25 locutionary speech act data. The dominant data produced in this research were 20 statement speech acts, then 3 command locutions and 2 question locutions. This research has the benefit of being a source of information to gain knowledge and understanding in the field of pragmatics, especially those related to locutionary speech acts.